Identifikasi Bakteri pada Luka Penderita Diabetes Melitus di Rumah Perawatan Luka Diabetes - Venny Patricia; Ahmad Yani; Salwa Salsabila; Rr. Sri Isjworowati (Poltekkes Kemenkes Semarang, 2023)
Diabetes mellitus (DM) is a metabolic disease that occurs due to hyperglycemia. In Indonesia it self, DM has a relatively high prevalence, this is evidenced because Indonesia is in the category of the top 10 countries in the world. The type of research used is descriptive research, namely identifying bacteria and testing sensitivity on wounds of diabetics with diabetes mellitus by performing cultures that are examined macroscopically and microscopically with the number of respondents obtained by as many as 17 people in 4 weeks. The results of this study obtained the prevalence of the types of bacteria that are (82.35%) gram-negative and (17.65%) gram-positive. The gram negatives included Proteus mirabilis (17.65%), Proteus morgani (5.88%), Citrobacter diversus (23.54%), Pseudomonas aeruginosa (11.76%), Escherichia coli (5.88%), Enterobacter agglomerans (5.88%) and Enterobacter cloacae (11.76%). While the gram-positive include Staphylococcus aureus (17.65%) with antibiotic sensitivity results whose sensitivity is in the yellow zone, which is around 50-75%, namely ciprofloxacin and meropenem antibiotics are in the green zone, which is around 76-100%.